Distribution and breeding of the White Stork (Ciconia ciconia) in North Macedonia in 2015 and 2016 - Putilin Stamkoska, Ksenija; Nakev, Slave; Uzunova, Danka; Arsovski, Borče; Arsovska, Ana; Velevski, Metodija (Macedonian Journal of Ecology and Environment, 2020)
The national White Stork census was conducted as part of the International Stork Census in an attempt to close the gap of 57 years since the last national census and establish a new basis for further conservation action. Total of 837 breeding pairs (HPa) were recorded during 2015/2016. Most of the pairs (534) bred in 45 colonies with 5 of more pairs. Five colonies with more than 20 pairs were found, along with 17 colonies of 11-20 pairs and 19 breeding colonies of 5-10 pairs. The total surface-based population density was 3.26 pairs/100 km2. The average biological density was 27.59 HPa/100 km2, but it varies widely at a regional level, with Tikveš region having the highest density of 106.7 pairs/100km2 and Maleš region having the lowest of 4 pairs/100 km2. Most of the nests (62.4%) were placed on overhead transmission pylons, followed by buildings (36.8%). Only 0.6% of the nests were placed in trees, and nesting on hay bales and stacks was completely absent. The number of pairs with fledged juveniles (HPm) was minimum of 717 for 2015 and 2016 combined. The breeding success (JZa) in 2015 was 2.78 ± 1.18 and the fledgling rate (JZm) was 2.97 ± 0.96. There were possibly significant differences in the breeding parameters among some of the regions.